Meningkatkan Kemampuan Sosial Emosional Anak Usia Dini melalui Permainan Menjaring Ikan - Sunandar Azma'ul Hadi (LP2M STIT Palapa Nusantara, 2021)
This study aims to improve children's social emotional skills through fishing games in group B PAUD KB Wanting Skilled Dusun Dasan Koak. Researchers chose this game to catch fish because the game of catching fish has never been implemented in PAUD KB Wants Skilled in improving children's social abilities. This type of research is qualitative research. The subjects in this study were 17 children of group B KB PAUD Want Skilled. The object of this research is the ability to interact, cooperate, and be responsible. Data collection methods used were observation, interviews, and documentation. The instrument used was the observation sheet. The data analysis technique was conducted in a descriptive qualitative manner. The results showed that the social emotional abilities of children increased after the action through fishing games. From the activity data before the research, it shows that the percentage of children's social emotional abilities is 23.52% or 4 children (BSH), 29.41% or 5 children (MB), and 47.05% or 8 children (MB). At the first meeting, the percentage of social emotional abilities increased to 29.41% or 5 children (BSB), 35.29% or 6 children (BSH), and 35.29% or 6 children (MB). At the next meeting, the percentage of social emotional abilities increased to 41.17% or 7 children (BSB), 47.05% or 8 children (BSH), and 11.76% or 2 children (MB). The game to catch fish is carried out in groups, there are groups that act as fish and there are groups that act as fishing nets. In group formation, the researcher involved the children by drawing and assigning two children to be the leaders in each group.